Methodological Approach and Stages of Preparing Elementary Students for the International Assessment Program - Utanbaeva Dildora Abdikhadirovna (International Journal of Formal Education, 2024)
this article covers the content of the work carried out in preparing elementary students for the PIRLS International Assessment Program, analyzes and subjectively reacts to the research of Methodist scientists who conducted scientific research on approaches such as the behaviorist approach, integrative approach, competency approach, logical approach, cognitive approach. Also, the opinions of psychologist and Methodist scientists on the stages of reading and understanding the text, its perception, assimilation are studied, and the stages of improving the methodology for preparing elementary students for the International Assessment Program are presented.